PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKN MELALUI METODE BERMAIN PERAN DI KELAS V SDN 07 TUANKU LINTAU - YUSTINAR YUSTINAR (JURNAL MANAJEMEN PENDIDIKAN, 2019)
The lack of active and low learning outcomes of Citizenship Education in the process of formulating Pancasila as the basis of the country due to the use of learning methods by conventional teachers and are less attractive to students, making student learning outcomes low. This type of research is a class action research (class action research), research using qualitative and quantitative approaches. The research procedure consists of stages: planning, implementation phase, observation phase, and reflection phase. The research data were obtained by writing tests and using observation sheets. The subjects of the study were the fifth grade students of SDN 07 Tuanku Lintau, Lintau Buo Utara District, Tanah Datar Regency in the first semester of 2016/2017 academic year as many as 16 people. The results showed that the role playing method (Role Playing) could improve the learning outcomes of Citizenship Education on the material for the formulation of Pancasila as the basis of the state in class V SDN 07 Tuanku Lintau, Lintau Buo Utara District Tanah Datar District with completeness in Cycle I completeness of students 62.5% The activities of teachers in teaching the first cycle 74.5% carried out and active students the first cycle 74.95%. After being reflected on the weakness in the first cycle there was an increase in the second cycle of students completeness 84.38%, teacher activity increased to 94% and students who were active 91%. From the research analysis it can be concluded that through the role playing method (Role Playing) can improve student learning outcomes in PKN learning in class V SDN 07 Tuanku Lintau, Lintau Buo Utara District.